GAMBARAN POLA MAKAN PADA LANSIA DENGAN DIAGNOSA HIPERTENSI - Nurhayati Nurhayati; Asra Hatlah (Nursing Arts, 2022)
Introduction: Elderly is a process of getting older with age reaching 45 years and over, the elderly will experience physical setbacks, one of the physical setbacks in the elderly is hypertension. Hypertension is an increase in arterial blood pressure where the systolic is more than 140 mmHg and the diastolic is more than 90 mmHg. One of the main causes of hypertension is irregular eating patterns. Purpose: This case study aims to describe the eating patterns of elderly people diagnosed with hypertension in the Maccini Sawah Community Health Center, Makassar City, in 2022. Method: Descriptive case study. Data collection was carried out through interviews, physical examination observations and documentation studies. Results: The results of the case study were found in the first and second respondents, namely that most of them had an eating pattern that did not meet health requirements because the two respondents still liked to eat foods with coconut milk, meat and salted foods (salted fish). Conclusion: After conducting a case study for 4 days, it can be concluded that both respondents have an eating pattern that does not meet health requirements because the two respondents have not been able to control their eating patterns. Keywords: Elderly; Hypertension; Diet